An Examination of Qur'anic Concept on Corruption - Budi Birahmat; Syarial Dedi (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The social problem that continues to be discussed endlessly today is a case of increasingly concerned corruption. Discussion of corruption problematics almost deadlocked because what made the eradication of corruption in this country is inversely correlated with the increasing index of corruption rank in Indonesia. Therefore, many people are more pessimistic about the eradication of corruption in Indonesia, even some of them are permissive. In addition, Corruption is also a crime classified as extra-ordinary crimes, because what resulted from corruption has brought a direct result, which is aggravating the poverty of the people. Some scholars began to track the Qur'an's affirmation of corruption. It is done as an effort to find epistemology eradication corruption case remember that al-Qur'an is holy book which give hint. Meanwhile, the Qur'an, which is still global and universal, remains a matter to be scrutinized and studied comprehensively. The discourse of corruption, for example, is still an implicit concept that is not clearly described by the Qur'an. But, it does not mean, the Qur'an can not solve this case.